2020
DOI: 10.1109/access.2020.2971586
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Autocorrelation Convolution Networks for Automatic Modulation Classification Based on Small Sample Set

Abstract: For modulation classification, hand-crafted approaches can generalize well from a few samples, yet deep learning algorithms require millions of samples to achieve the superior performance with purely data-driven manner. However for many practical problems only with small sample set (SSS) available, there still remains a challenge for deep learning. In this paper, we employ deep learning to solve the modulation classification task in a more practical setting, particularly suffering from the SSS problem and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It is found that the functions of different algorithms are varied, indicating that each algorithm has different application scenarios. Although deep learning plays a dominant role in the field of machine vision, deep learning is data-driven and has poor performance in small datasets [52][53][54]. However, traditional machine learning can adapt to a variety of datasets; especially in scenarios with small amounts of data (such as the medical field), machine learning has better performance [55,56].…”
Section: Classical Machine Learningmentioning
confidence: 99%
“…It is found that the functions of different algorithms are varied, indicating that each algorithm has different application scenarios. Although deep learning plays a dominant role in the field of machine vision, deep learning is data-driven and has poor performance in small datasets [52][53][54]. However, traditional machine learning can adapt to a variety of datasets; especially in scenarios with small amounts of data (such as the medical field), machine learning has better performance [55,56].…”
Section: Classical Machine Learningmentioning
confidence: 99%
“…As an alternative to the conventional methods mentioned above, in recent years, deep-learning (DL)-based techniques employing neural networks (NNs) have been explored for classifying signals using specific features that can be extracted from the data [ 17 , 18 , 19 , 20 , 21 , 22 ]. We note that NNs require extensive training to become proficient and that, depending on the type of NNs and features used, overfitting and a lack of generalization can affect the robustness of the trained NNs such that their performance degrades when presented with inputs that have different probability distributions than those in the training dataset.…”
Section: Introductionmentioning
confidence: 99%